The performance of initial public offer versus performance of privatised government companies - Tenang, Zambri Mohamad (1998)
The empirical evidence accumulated during recent years for almost every capital market in the world suggested that initial public offering provide significant abnormal return on their first day of trading. This study, however, has three major objectives. First, to determine the general trends of underpricing of IPO's from 1987 to 1997. This is because there is a genet al fiend that IPO's has become popular among investors in Malaysia. The second is to determine the possible factors that might have contributed to the level <»r iKidcmiising. 'Ihiidly, to compile the general trends against privatised governin' nt companies. This study documents a mean annualised first day return of 10,560 percent Tor privatised government companies, 241,793 percent for companies on the main board, and 5,355,436 percent for second board companies. The oversubscription ratio was 7.6 times for government companies, 33.9 times for main board companies and 60.1 times for the second board companies. The observation seems to indicate that the larger the size of a company , the lower is its oversubscription ratio and the first day return on investment. The study also indicates that the company opening price has a very strong relationship to the subscription price of the stock, the gross price earning ratio based on subscription price and the number of times it is oversubscribe. The result of this study is consistent with the study done by Yong (1996) on IPO's of Malaysian stock, and not consistent with the study done by Perotti (1993) on the structure of privatisation plans.